Pokok Anggur yang Benar: Eksegesis terhadap Yohanes 15:1-3 - Daniel Horatius Herman (Sekolah Tinggi Teologi Kalimantan, 2020)
The various interpretations of John 15:1-3 point to errors in the method of interpretation. Of course, Jesus only had one purpose. This research aims to find the meaning of the true teachings of Jesus that will lead every believer to the true Christian life, so that the wrong meaning, which confuses Christian to Understand the teachings of Jesus, can be anticipated. This study uses a hermeneutic research method that specifically exegesis to the discussion texts. This research examines the context of Jesus in the Gospel of John as a whole; the Old Testament context relating to John 15:1-3; and reviews in general, the context of the chapters around John 15:1-3 and concludes based on these steps. John 15:1, explains Jesus' statement as Yahweh and the statement of Jesus as the embodiment of Israel. John 15:2a describes “the cut branches” referring to all Israelites who rejected Jesus. Meanwhile